Hepatoprotective effects of Psidium guajava on mitochondrial enzymes and inflammatory markers in carbon tetrachloride-induced hepatotoxicity. (1st December 2020) - Vijayakumar, Kalaiyarasan; Arumugam, Vijaya Anand; Ramasamy, Manikandan; Natesan, Manoharan; Palanisamy, Sampathkumar; Thajuddin, Nargis Begum; Balasubramanian, Balamuralikrishnan; Meyyazhagan, Arun
Abstract: Objective: The present investigation was aimed to evaluate the hepatoprotective potential of ethanolic extract of Psidium guajava ( P. guajva ) and its isolated quercetin fraction on carbon tetrachloride (CCl4 )-induced hepatotoxicity. Materials and methods: The rats were divided into 6 groups and each group contained 6 rats. CCl4 (1.5 ml/kg b.w.) was used to induce the hepatotoxicity. Ethanolic extract of P. guajava (300 mg/kg b.w.), isolated quercetin fraction (20 mg/kg b.w.) were used as a treatment and silymarin (25 mg/kg b.w.) was used as a standard drug. After the study period, the liver tissues were collected and evaluate the levels of liver functional markers, mitochondrial enzymes, histopathological analysis and the expressions of inflammatory markers. Results: The levels of liver functional markers were increased and protein, albumin and A/G ratio levels were decreased and the decreased levels of mitochondrial enzymes were noted in CCl4 -induced rats and the levels were restored near to normal significantly when the administration ethanolic extract of P. guajava, isolated quercetin fraction and silymarin. The normal architecture of liver tissues were altered and the mRNA expressions were up-regulated in CCl4 -induced rats and the liver tissues were normalized and the mRNA and protein expressions were down-regulated near to normal significantly when the administration of ethanolic extract of P. guajava, isolated quercetin fraction and silymarin. Conclusion: From these results, the isolated quercetin fractions have better activity than that of the ethanolic extract of P. guajava leaves. Hence, the isolated quercetin may be used as the safest drug for hepatotoxicity in future.